Comparative study of the drying of pears using different drying systems. - Guiné, Raquel (2012)
The present work studies different methods for the drying of pears, namely a solar stove, a solar dryer and a tunnel dryer. All processes were conducted in three consecutive years to analyze if the behavior of each drying method shows evidence of a similar pattern, and if they allow the obtaining of products as much as possible similar to the traditional pears that are dried at direct sun exposure. The results have allowed us to conclude that all methods have lead to a considerable reduction in drying time as compared to open-sun drying. Indeed, the drying time for the solar stove and the solar dryer showed a reduction of more than 40% while in the drying tunnel this reduction increased to more than 60%. In addition, it was also possible to conclude that the properties of the dried pears obtained by the three processes correspond to dried fruits similar to the traditional dried pears.